The use of optically activated nanoparticles to enhance controlled lesion formation from high intensity focused ultrasound exposures - McLaughlan, J; Murray, T; Roy, R (IEEE, 2011)
Light-absorbing nanoparticles can be used to improve the signal-to-noise ratio of the thermoelastic emissions from tissue that are used in photoacoustic tomography (PAT) and microscopy (PAM). Nanoparticles can be functionalized to selectively target cancer cells and destroy them through the formation of vapour bubbles. It has been shown that heating of the nanoparticles with a laser whilst they are simultaneously under tension from a high intensity focused ultrasound (HIFU) field results in a significant reduction in the optical fluence and acoustic pressure thresholds required for bubble formation. The localised heating from HIFU exposures in tissue is believed to be increased through the presence of bubbles, or specifically inertial cavitation, in the focal region. Thus an ability to nucleate vapour bubbles from nanoparticles using laser light combined with a HIFU field presents a unique opportunity for imaging and therapeutic applications.